Pengaruh Komunikasi dan Budaya Organisasi terhadap Kinerja Karyawan Head Office PT. TELKOMSEL - Ary Ferdian; Luisa Putri Amanda Charitas (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
The purpose of this study was to find out how the level of communication, organizational culture, and employee performance, and to determine the effect of communication and organizational culture simultaneously or partially on employee performance in the head office of PT. Telkomsel. The research method used is a quantitative method. Primary data collection techniques with interviews, observations, and questionnaires. Samples were selected as many as 92 employees from a total population of 1,194 employees using simple random sampling technique with the Slovin formula. The analysis technique in this research is descriptive analysis, classic assumption test, and multiple linear regression analysis and coefficient of determination test. Descriptive analysis results show that communication, organizational culture, and employee performance at the head office of PT. Telkomsel are classified as good. Based on the results of hypothesis testing using the t test shows that the communication variables and organizational culture partially have a significant effect on employee performance. While simultaneous hypothesis testing with the F test shows that simultaneous communication and organizational culture significantly influence employee performance. The magnitude of the influence of communication and organizational culture on the performance of PT. Telkomsel is 66.42% and the remaining 33.58% is influenced by other variables.